Criminal Law Theory Indonesia - Nurul Fadhilah (Journal of Strafvordering Indonesian, 2024)
This article discusses the concept of understanding crime through the chronological paradigm, which involves analyzing the evolution and development of crime over time. This paradigm outlines a series of crime events to reveal the factors that influence and encourage crime. Looking at crime chronologically allows for an understanding of changes in crime patterns, societal responses, and prevention and countermeasure efforts that have been made. Chronological analysis traces crime patterns in the context of certain historical events or social crises, providing insight into how social conditions influence criminal behavior. Societal responses to crime shape criminal policy and future prevention efforts. The evolution of legal systems and changes in social norms are reflected in the way crime is defined and punished. Through collaboration between researchers, law enforcement, and policy makers, understanding the chronology paradigm helps identify common patterns, respond to changes in society, and develop more effective strategies in tackling crime.